Dental Intervention Perspective: Anatomical Variation Of Mental And Mandibular Foramen In Selected Malay Patients - Bunyarit, S. S.; Ying, R. P. Y.; Kadir, B. A.; Nizam, M. M.; Rahman, M. (Ibn Sina Trust, 2024)
Bangladesh Journal of Medical Science Vol. 15 No. 03 July’16